Media at war : the Iraq crisis - Tumber, Howard (Sage Publications, 2004)
The Iraq war provoked widespread public debate, and media coverage of the events have also been the subject of scrutiny. Embedded reporters, 24-hour news and 'live on the spot' reports have had a huge impact on the news we receive. Media at War offers a critical overview of the war coverage, and provides a context for examining questions that emerged about the role of journalists: What experience, training and protection do war reporters have? What is the relationship between journalists and their sources? Are embedded journalists able to deliver balanced news coverage?